Odpowiedzi

2009-12-07T16:58:02+01:00
1.
x(do kwadratu)=4
x+y=2

x(do kwadratu)=4 CZYLI x=2
x+y=2

Teraz Przenosimy ze zmienionym znakiem:

x=2
y= -x-2

czyli podstawiamy:
x=2
y= -2-2

x=2
y=-4

1 1 1
2009-12-07T20:18:46+01:00
X²=4
x+y=2

x=√4=2
x+y=2

x=2
2+y=2

x=2
y=2-2

x=2
y=0
1 4 1
Najlepsza Odpowiedź!
2009-12-07T21:48:46+01:00
A)
x²=4
x+y = 2
x=√4
y= 2-x
x=2
y= 2-2
y=0

b)
(x-1)do potęgi 7 = -1
y²-x = 9
x do 7 - 1 = -1
y²= 9+ x
x do 7 =0
y²= 9+x
x=0
y² = 9 + 0
y = √9
y = 3

c)
y - x²= 4
y + x² = 12
2y = 16
y= 8
8+ x² = 12
x²= 4
x= 2